2022
DOI: 10.1093/geroni/igac059.2084
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Aging and Successful Aging: The Role of Memory

Abstract: The cognitive functioning as a general measure, is a criterion commonly used to define and operationalize successful aging(SA). This study aims to explore the specific contributions of the memory and meta-memory to understanding successful aging (SA).(Project-Conacyt-256589)Population based, random sample included n=656 community-dwelling older adults 60-years and older (mean age=72.8, SD=7.6 years, 58% women). Memory was measured with the Digit span test backward (WAIS-IV). and meta-memory through self-report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This comprehensive understanding involves examining various cognitive domains and their impact on successful ageing. A study of 656 community-dwelling individuals aged 60 and over found that memory and meta-memory significantly contribute to both objective and subjective successful ageing (Ruvalcaba, Arias-Merino, Díaz, & Flores-Villavicencio, 2022). It suggests that interventions to improve memory and foster positive perceptions of one's memory could potentially enhance successful ageing outcomes in older adults.…”
Section: Cognitive Functionmentioning
confidence: 99%
“…This comprehensive understanding involves examining various cognitive domains and their impact on successful ageing. A study of 656 community-dwelling individuals aged 60 and over found that memory and meta-memory significantly contribute to both objective and subjective successful ageing (Ruvalcaba, Arias-Merino, Díaz, & Flores-Villavicencio, 2022). It suggests that interventions to improve memory and foster positive perceptions of one's memory could potentially enhance successful ageing outcomes in older adults.…”
Section: Cognitive Functionmentioning
confidence: 99%